Evaluation of the hygiene status in several meat and dairy processing establishments in R. Macedonia - Ratkova Marija; Prodanov Mirko; Angelovski Ljupco; Jankuloski Dean; Sekulovski Pavle; Mojsova Sandra (Macedonian Veterinary Review, 2013)
The hygiene practice is one of the most important aspects in the production of safe food. The effectiveness of the cleaning and disinfection programs can be evaluated by continuous examination of the microbiological counts of the surfaces and hands of the workers by taking swabs.In a period of 6 months, 717 swabs were examined, 600 of them from working surfaces, and 117 from employees hands, by using the standard swabbing technique. From the meat production premises 453 swabs were sampled from surfaces and 94 swab samples from workers hands. At the dairy establishments, 147 swabs were taken from the surfaces and 23 swabs from employees hands. The samples were tested for total bacteria viable count according to ISO 4833:2003 and the enumeration of Enterobacteriaceae according to ISO 21528-2:2004, and after that the results were evaluated in accordance with Directive 471/2001/EEC. Obtained results from the meat processing plants were the following: 15.6% were unacceptable for total viable count (TVC) and 7.5% were unacceptable for enumeration of Enterobacteriaceae from the swabs taken from surfaces, and 10.6% and 2.1% respectively from the swabs taken from their workers. The results in the milk processing premises were: 9.5% unacceptable for TVC and 2% unacceptable for enumeration of Enterobacteriaceae from the swabs from their surfaces, and 17.4% and 8.7% respectively from the swabs taken from their workers.The results are indicating that although there is a high level of appropriate hygiene practice in all of the food production premises, there is still a percent of unacceptable results, which suggests a lack of hygiene and can emphasis the need for further improvement of the cleaning and disinfecting techniques especially for the surfaces in the meat processing premises and an improvement in the personal hygiene in the dairy industry.